Pengaruh Tingkat Pendidikan Orangtua Terhadap Kemampuan Numerasi Siswa SD UPT SDN 72 Gresik - Wilwan Tikta Sari, Paringga; Ismawati, Desi; Indrawan, Nindi; Zakiatun Nissa, Heppy (J-SES : Journal of Science, Education and Studies, 2025)
Parental education is considered to play a significant role in the development of children's academic abilities, including early numeracy skills. This study was conducted at UPT SDN 72 Gresik to examine the influence of parents' educational level on students' numeracy skills. The research aims to determine whether there is a significant relationship between parents' educational level and the numeracy skills of Group B students at UPT SDN 72 Gresik. The study employs a quantitative method with a linear regression approach. The sample consists of 11 Group B students, with data collected through numeracy tests for students and questionnaires for parents. Regression analysis results reveal that parents' educational level significantly impacts students' numeracy skills. Parents' educational level accounts for 51.9% of the variation in students' numeracy skills, with each one-unit increase in educational level enhancing children's numeracy skills by 0.625 units. The study concludes that parents' educational level significantly influences the numeracy skills of young children at UPT SDN 72 Gresik. Parents with higher education levels tend to be more effective in supporting their children's numeracy development. Keyword: Parental education, numeracy skills, early childhood, linear regression